Augmented Reality-Based Learning Media Application for Introducing West Sumatran Culture - Wieke Ricesa; Devy Sri Wahyuni (Yayasan Pendidikan Bustanul Ulum Mojokerto, 2026)
The rapid development of information and communication technology has brought various innovations in the field of education, including the utilization of Augmented Reality (AR) for learning. This research aims to develop an Augmented Reality-based application for introducing the culture of West Sumatra, which can be used as an interactive learning medium. The method used in the development of this application employs Unified Modeling Language (UML) for system design. This research utilizes Marker-Based AR technology. The application is developed using Unity 3D and displays 3D objects that represent elements of West Sumatra's culture. In this study, the application was tested using the User Acceptance Test (UAT) method, yielding a result of 93%. This indicates that the application is helpful in understanding the culture of West Sumatra and is effective as a learning media tool.